Sources of Information on Flood-Resistant Design and Construction - Carol Fountain; Michael T. Olexa; Jana Caracciolo; Lauren Grant (EDIS)
This 2-page fact sheet is a minor revision. The primary purpose of the publications referenced in this article is to assist engineers, architects, contractors, and property owners in locating detailed information on how to design and construct flood-resistant buildings and structures. Written by Michael T. Olexa, Jana Caracciolo, and Lauren Grant, and published by the the Food and Resource Economics Department, October 2019.